Three-Dimensional Bi2Fe4O9 Nanocubes Loaded on Reduced Graphene Oxide for Enhanced Electromagnetic Absorbing Properties - Lu, Min; Sun, Yuan-Kai; Yang, Shu-Hao; Wang, Hui-Ya; Guan, Xiao-Hui; Wang, Guang-Sheng (Frontiers in Chemistry, 2020)
Bi2Fe4O9(BFO) nanocubes have been prepared in proportion by a simple and easy hydrothermal method, and then the BFO nanocubes were assembled on the reduced graphene oxide (rGO) multilayered sheets. The excellent microwave absorption properties of Bi2Fe4O9/rGO nanohybrids were achieved by properly adjusting impedance matching and getting high attenuation capability contributed from different ratios of the BFO and rGO. A minimum reflection loss value of -61.5 dB at 12.8 GHz was obtained with Bi2Fe4O9/rGO ratio of 2:1, and the broadest bandwidth below -10 dB is up to 5.0 GHz (from 10.8 to 15.8 GHz) with a thickness of 2.4 mm. Additionally, elementary mechanism of wave absorption performance is also investigated.